Quantitative changes within the peripheral blood CD8highCD57+ T-cell subpopulation of patients with advanced renal cell carcinoma - Strioga, Marius; Pašukonienė, Vita; Dobrovolskienė, Neringa; Petraitis, Tadas; Kazlauskaitė, Nijolė; Darinskas, Adas; Jokubauskienė, Lina; Characiejus, Dainius (Acta medica Lituanica, 2014)
Background. Antitumor immunotherapy strategies, such as cytokine- based or cell-based immunotherapies, are designed to activate immune response against cancer cells, but considering that malignancy may be associated with the expansion of immunosuppressive components of antitumor immunity, it is likely that in such cases activation of the immune system would further enhance activity of these components, leading to more severe suppression of antitumor immune response thus making more favourable conditions for tumor progression. Materials and methods. We studied the expression of biomarkers, representing immunosuppressive (FOXP3) and cytotoxic (perforin, IFN-γ) CD8highCD57+ T-cell subpopulation functions in the peripheral blood of 34 patients with advanced clear cell renal cell carcinoma (RCC) and 26 controls by multicolour flow cytometry. Results. CD8highCD57+ T cell subpopulation of all CD8+ T cells in RCC patients was significantly higher compared to age-matched healthy controls (p = 0.003). It was found that the mean percentage of suppressive CD8highCD57+FOXP3+ T-cell subset and cytotoxic CD8highCD57+Perforin+ T-cell subset in the CD8highCD57+ T-cell subpopulation was significantly increased in RCC patients compared to controls (p = 0.0004 and p = 0.008, respectively). There was no strong and biologically relevant negative correlation between the expression of FOXP3 and Perforin in the peripheral blood CD8highCD57+ T-cell subpopulation of RCC patients. Conclusions. Subsets of immunosuppressive FOXP3+ T cell and tumor-attacking (cytotoxic) Perforin+ T cells in the CD8highCD57+ T-cell subpopulation are significantly increased in RCC patients compared to controls. These quantitative rearrangements are independent and individual for each RCC patient.
Keywords: CD8highCD57 T cells; cytotoxic subsets; immunosuppressive subsets; renal cell carcinoma; individualized antitumor immunotherapy